2007
DOI: 10.1128/mcb.01643-06
|View full text |Cite
|
Sign up to set email alerts
|

mRNAs Encoding Polarity and Exocytosis Factors Are Cotransported with the Cortical Endoplasmic Reticulum to the Incipient Bud in Saccharomyces cerevisiae

Abstract: Polarized growth in the budding yeast Saccharomyces cerevisiae depends upon the asymmetric localization and enrichment of polarity and secretion factors at the membrane prior to budding. We examined how these factors (i.e., Cdc42, Sec4, and Sro7) reach the bud site and found that their respective mRNAs localize to the tip of the incipient bud prior to nuclear division. Asymmetric mRNA localization depends upon factors that facilitate ASH1 mRNA localization (e.g., the 3 untranslated region, She proteins 1 to 5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
144
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(151 citation statements)
references
References 72 publications
(133 reference statements)
7
144
0
Order By: Relevance
“…In contrast, other peroxin mRNAs, such as PEX6, 10, and 27-29, showed a low level of colocalization with peroxisomes (33%, 30%, 32%, 40%, and 32%, respectively), while some (i.e., PEX2, 7,17,18,22,30, and 32) showed little to no colocalization (6%, 5%, 24%, 18%, 18%, 16%, and 20%, respectively; Fig. 1 A and Table S2).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…In contrast, other peroxin mRNAs, such as PEX6, 10, and 27-29, showed a low level of colocalization with peroxisomes (33%, 30%, 32%, 40%, and 32%, respectively), while some (i.e., PEX2, 7,17,18,22,30, and 32) showed little to no colocalization (6%, 5%, 24%, 18%, 18%, 16%, and 20%, respectively; Fig. 1 A and Table S2).…”
Section: Resultsmentioning
confidence: 98%
“…The reason for this is unclear, but it could be due to the elevated levels of POT1 mRNA in the cell lysate or because the MS2L sequence interferes with POT1 mRNA localization. Importantly, mRNAs known to localize with cortical ER (i.e., CDC42 and SEC4) (7) were not observed in the peroxisome fraction, although SEC61 mRNA was. This may represent nuclear ER contamination; studies have shown that peroxisomes are derived from ER (19).…”
Section: Subcellular Fractionation Of Peroxisomes and The Detection Omentioning
confidence: 95%
See 2 more Smart Citations
“…She3p contains at least three binding modules, one for Myo4p and two for cargos, as diverse as zipcoded mRNP and tubular endoplasmic reticulum (tER) (27)(28)(29). She3p's binding site for Myo4p has been localized to the middle region of She3p (30), with a genetically determined upstream binding site for tER and a downstream binding site for zipcoded mRNP (29).…”
Section: Significancementioning
confidence: 99%